The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/rec.13112
|View full text |Cite
|
Sign up to set email alerts
|

Successional dynamics of soil fungal diversity along a restoration chronosequence post‐coal mining

Abstract: Soil disruption from open-cut mining practices can adversely impact microbial communities and the ecosystem services that they mediate. Despite this, assessment of impacts of soil disruption, and the subsequent recovery of microbial communities is rarely studied. Monitoring of ecological restoration success on mine sites has traditionally focused on vegetation; however, most plants rely, at least in part, on associations with soil fungi for enhanced nutrient and water acquisition. Here, we used highthroughput … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 50 publications
(104 reference statements)
0
9
2
Order By: Relevance
“…Increased soil pH under rehabilitation would favour fungal over bacterial decomposition (Angel et al, 2013; Tedersoo et al, 2014), which accords with both the greater fungal biomass with time since rehabilitation (Figure S8.2) and the increase in AMF biomass with increasing pH (Figure S8.5). We also found that fungal diversity was greater in soils at reference (1,088 ± 134, M ± SD ) than rehabilitated (974 ± 210) sites, unlike studies from other mine site restoration studies (Ngugi et al, 2019). Fungi are critically important in the restoration process because they recycle organic matter, improve soil structure, ameliorate metal tolerance in plants, and enhance water holding capacity (Delgado‐Baquerizo et al, 2019; Ngugi et al, 2019).…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Increased soil pH under rehabilitation would favour fungal over bacterial decomposition (Angel et al, 2013; Tedersoo et al, 2014), which accords with both the greater fungal biomass with time since rehabilitation (Figure S8.2) and the increase in AMF biomass with increasing pH (Figure S8.5). We also found that fungal diversity was greater in soils at reference (1,088 ± 134, M ± SD ) than rehabilitated (974 ± 210) sites, unlike studies from other mine site restoration studies (Ngugi et al, 2019). Fungi are critically important in the restoration process because they recycle organic matter, improve soil structure, ameliorate metal tolerance in plants, and enhance water holding capacity (Delgado‐Baquerizo et al, 2019; Ngugi et al, 2019).…”
Section: Discussioncontrasting
confidence: 75%
“…We also found that fungal diversity was greater in soils at reference (1,088 ± 134, M ± SD) than rehabilitated (974 ± 210) sites, unlike studies from other mine site restoration studies (Ngugi et al, 2019). Fungi are critically important in the restoration process because they recycle organic matter, improve soil structure, ameliorate metal tolerance in plants, and enhance water holding capacity (Delgado-Baquerizo et al, 2019;Ngugi et al, 2019). Future work needs to further investigate how to trigger the restoration of soil microbial diversity, a major driver of ecosystem functioning, to help in achieving maximum levels of ecosystem recovery after disturbance.…”
Section: Limited Recovery Of Biotic and Functional Attributes Relativ...contrasting
confidence: 76%
“…On the other hand, several studies have been conducted on fungal community response to restoration chronosequence. Whlist Ngugi et al [ 62 ] demonstrated that fungal communities eventually became more similar to the reference condition over time, Kane et al [ 63 ] found no obvious trend in fungal diversity toward the reference forest. However, both investigations found that the fungal community was mostly shaped by edapic variables [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ecological restoration process of mines is relatively long, and it is very necessary to monitor and evaluate the ecological characteristics of the restoration process. In the early stage, the evaluation and monitoring of the restoration effect of mining area mostly depend on the physicochemical properties of aboveground vegetation and soil [25,26]. Although soil microorganisms were affected by mining activities and had a regulatory role in ecosystem function, they were rarely monitored in prior research studies [27,28].…”
Section: Introductionmentioning
confidence: 99%